Power Devolution and Electricity Transmission in Nigeria: A Study in Resources Mobilization for Economic Development - Obiora, Charles A.; Chiamogu, Amobi P.; Chiamogu, Uchechukwu P. (Advances in Social Sciences Research Journal, 2019)
The 1979 and 1999 constitutions of Nigeria created anti-development frameworks that unhealthily endowed the federal government with excessive powers in direct contravention of the most basic tenets of federalism. One of the items that has remained subtly contrived in the exclusive list is power generation. The 2005 Electric Power Sector Reform Act through Sections 8, 65 and 66 established and licensed Transmission Company of Nigeria (TCN) to take charge of transmission and system operation of high voltage network of the Nigerian electricity supply industry. Thus, the Nigerian energy policy structure continues to be top-down involving huge investments in large electricity mega plants, generating electricity into mega grids for mega distribution. Based mainly on secondary sources of data, this paper is a descriptive and analytical clarification of issues on power sharing as key impediment to poor electricity generation, transmission and distribution in Nigeria. The study examines the implications of power behemoth federal government that stifles autonomy of federating units in Nigeria. It observes that the exclusive right to electricity transmission by the federal government negates sustainable electric power supply in Nigeria. It therefore recommended devolution of powers and streamlining of Second Schedule of 1999 Constitution to reflect a true federal system